2008
DOI: 10.17161/bi.v5i0.39
|View full text |Cite
|
Sign up to set email alerts
|

Where and how to manage: Optimal selection of conservation actions for multiple species.

Abstract: Abstract.-Multiple alternative options are frequently available for the protection, maintenance or restoration of conservation areas. The choice of a particular management action can have large effects on the species occurring in the area, because different actions have different effects on different species. Together with the fact that conservation funds are limited and particular management actions are costly, it would be desirable to be able to identify where, and what kind of management should be applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The absence of strong positive correlations suggested that any prioritization would need to consider habitat indices for all three habitats, rather than one habitat acting as a surrogate for the others. These results illustrate the need to design restoration and conservation efforts such that a range of high quality habitats are conserved and managed to support a broad suite of species (Teefelen and Moilanen 2008;Stralberg et al 2009). …”
Section: Comparing Site Rankings For the Three Habitatsmentioning
confidence: 90%
“…The absence of strong positive correlations suggested that any prioritization would need to consider habitat indices for all three habitats, rather than one habitat acting as a surrogate for the others. These results illustrate the need to design restoration and conservation efforts such that a range of high quality habitats are conserved and managed to support a broad suite of species (Teefelen and Moilanen 2008;Stralberg et al 2009). …”
Section: Comparing Site Rankings For the Three Habitatsmentioning
confidence: 90%
“…The algorithm then iteratively searched through the remaining combinations until it exhausted a simulated conservation budget. A detailed description of this approach can be found in van Teeffelen and Moilanen () and van Teeffelen et al (). For each of the k colonies and l actions, we predicted a unique expected response, x kl .…”
Section: Methodsmentioning
confidence: 99%
“…Arponen et al . (2005) and Van Teeffelen & Moilanen (2008) tested various shapes of benefit functions (linear, ramp, concave and sigmoid). In this study, we used a concave benefit function because it tends to push species representation to higher levels and results in higher representation levels for rare species than other functions (Arponen et al.…”
Section: Methodsmentioning
confidence: 99%